Immunogenicity risk assessment of peptide-related impurities identified in generic teriparatide products - Mattei, Aimee E.; Roberts, Brian J.; Lelias, Sandra; Miah, Shah; Howard, Kristina E.; Weaver, James L.; Verthelyi, Daniela; Pang, Eric S.; Edwards, Katie; De Groot, Anne S. (Frontiers in Immunology, 2025)
Teriparatide is one of several generic peptides named in a recent Food and Drug Administration (FDA) guidance (FDA-2017-D-5767-0002), which outlines a potential strategy to inform immunogenicity risk assessment for synthetic generic peptides without requiring clinical studies. Specifically, the guidance states that for abbreviated new drug applications (ANDAs), once the sameness of the active pharmaceutical ingredient (API) between the generic product and the reference listed drug is established, developers can mitigate the residual risk of unwanted immunogenicity response by using in silico and in vitro tools to characterize differences in product- and process-related impurities between the reference and generic drug products. Regarding product-related impurities, a stated concern is that sequence modifications may create new T-cell epitopes capable of driving unwanted immune responses. Specifically, the guidance sets limits for the relative abundance of each impurity and requests that any new impurity above a certain concentration threshold be evaluated for potential T-cell-driven immunogenicity using orthogonal methods that assess both human leukocyte antigen (HLA) binding and the capacity to elicit a T-cell response. One such orthogonal immunogenicity risk assessment approach was applied to teriparatide (TPT) and several theoretical or observed product-related impurities in the case study described here. First, the immunogenic potential of TPT and selected impurities was assessed using three in silico tools: EpiMatrix, ClustiMer, and JanusMatrix. Second, an in vitro method was used to evaluate the binding affinity of TPT and the selected TPT impurities to different class II HLA-DRs in vitro. Third, a human peripheral blood mononuclear cell (PBMC) T-cell assay compared T-cell proliferation in response to individual impurities or the reference teriparatide drug product, Forteo®, in vitro. The orthogonal approaches identified multiple impurities as more immunogenic than TPT. In a novel finding, the in silico analysis revealed a potentially tolerogenic sequence in TPT, which correlated with lower-than-expected de novo immune responses to TPT in vitro. The analysis and methods described in this case study may help assess the relative risk of impurities and help identify those with the potential to increase the immunogenicity risk of a generic peptide.